2016
DOI: 10.1002/lary.26096
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term antibiofilm activity of carboxymethyl chitosan on mixed biofilm on silicone

Abstract: NA Laryngoscope, 126:E404-E408, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…[1][2][3][4][5] Management of an implant-associated infection often necessitates multiple debridement surgeries, implant replacement or removal, and long-term antibiotic treatment. [6][7][8][9] These problems are aggravated in patients with bone healing disorders associated with rheumatoid arthritis, osteoporosis, diabetes, or aging due to the difficulty of clearing an infection from poorly vascularized bone tissues and other necrotic tissues. 3,5,10,11 Implant-associated infections are caused by bacterial adhesion to an implant surface and subsequent formation of biofilms around implanted devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Management of an implant-associated infection often necessitates multiple debridement surgeries, implant replacement or removal, and long-term antibiotic treatment. [6][7][8][9] These problems are aggravated in patients with bone healing disorders associated with rheumatoid arthritis, osteoporosis, diabetes, or aging due to the difficulty of clearing an infection from poorly vascularized bone tissues and other necrotic tissues. 3,5,10,11 Implant-associated infections are caused by bacterial adhesion to an implant surface and subsequent formation of biofilms around implanted devices.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, carboxymethyl chitosan (CM-chitosan) might be a possible antibiofilm agent to be applied on voice prostheses. Tan and colleagues [158] performed several studies using this compound. They determined the influence of carboxymethyl chitosan on the mixed biofilm formation of C. albicans, C. tropicalis, L. gasseri, S. salivarius, R. dentocariosa, and S. epidermidis, on silicone over a long-term period.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 99%
“…from adhering to surface of medicinal silicone rubber (such as voice prostheses) and inhibit the evolution of mixed fungi biofilm at different stages for a long period of time in vitro. 82 , 83 Recently, Tan et al have revealed that CM-chitosan has exerted a strong inhibitory effect on the biofilm formation of non- C. albicans species including C. tropicalis , Candida krusei , C. parapsilosis and C. glabrata , particularly on mixed-species biofilm. 84 Yet, there is pressing need for further studies to explore whether medicinal silicone coated with CM-chitosan has an inhibitory effect on mixed fungal biofilm in vivo.…”
Section: Other New Drugsmentioning
confidence: 99%